Intermediate and long-term outcomes of transcatheter closure of congenital coronary cameral fistulas in 66 children - Li, Y F (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To evaluate the intermediate and long-term outcomes and technical aspects of transcatheter closure (TCC) of coronary cameral fistulas (CCF) in pediatric patients. Methods: This was a case-control study. All pediatric patients with CCF who underwent TCC between January 2005 and December 2019 were retrospectively reviewed. Data was collected from medical records, including demographic characteristics, procedural details, intraoperative and postoperative serious adverse events, follow-up results and prognosis. Patients with serious adverse events and without serious adverse events were compared regarding their clinical features and CCF characteristics. Comparisons between groups were performed with independent sample t test, chi-square test or Fisher exact test. Results: A total of 66 CCF patients (34 boys, 32 girls, 3.9 (1.9, 6.2) years old, 15 (11, 20) kg) underwent attempted TCC. All of the CCF were all medium or large fistulas including 55 proximal fistulas (83%) and 11 distal fistulas (17%). The CCF originated more frequently from the right coronary artery (38 cases (58%)), followed by the left coronary artery (28 cases (42%)). The incidence of coronary artery aneurysms (CAA) was 61% (40/66).Procedural treatment was achieved in 64 patients and procedural success was achieved in 59 patients (92%). Six (9%) serious adverse events occurred in 5 patients during the perioperative period. Acute complications included procedure-related death in one patient and acute myocardial infarction in one patient. Periprocedural complications occurred in 3 patients at one day postoperatively including acute myocardial infarction (2 cases), occluder detachment (1 case), and tricuspid chordae tendinae rupture (1 case). Clinical follow-up data were available in 58 of the 62 patients who underwent initial successful TCC with a follow-up period of 9.3 (6.5, 13.4) years. Ten adverse events occurred in 9 patients including 5 complications consisted of aortic valve perforation (1 case), coronary thrombosis (1 case), progressive aneurysmal dilation after reintervention (1 case), and new-onset tricuspid valve prolapse with significant regurgitation (2 cases) and large residual shunts due to fistula recanalization (5 cases). Therefore, the incidence of intermediate and long-term adverse events was 17% (10/58). During the periprocedural and follow-up period, 16 adverse events occurred in 13 patients, whereas no adverse events occurred in 51 patients. Patients with seriovs adverse events presented with larger proportion of large CCF (11/13 vs. 39% (20/51), P=0.005), giant CAA (10/13 vs.14% (7/51), P=0.030), and higher mean pulmonary artery pressure ((20±9) vs.(16±6) mmHg, 1 mmHg=0.133 kPa, t=2.02, P=0.048) compared to patients without serious adverse events. Conclusions: TCC in CCF children appears to be effective with favorable intermediate and long-term outcomes. Strict indication of TCC is mandatory